The investigation of tribological behavior of carbon fiber-reinforced composite materials. Issue 2 (17th December 2018) - Kaya, İsmail; Parlar, Zeynep
Abstract : Purpose: The tribological behavior of composites varies on matrices materials, the reinforcement material and the direction of reinforcement materials. The purpose of this study is to examine the effects of fiber orientation on the tribological properties of carbon fiber–reinforced epoxy composite. Design/methodology/approach: The experiments were carried out with a pin-on-ring tribometer. The tests were executed according to three different parameters: load, sliding velocity and direction of reinforcement. Loads measuring 92 N and 150 N were applied at sliding velocities of 1 and 2 m/s, in parallel, antiparallel and normal directions of fiber reinforcements. The frictional force was read every 500 m of sliding distance. To calculate specific wear rate, the mass of the samples was measured before and after each experiment. Moreover, temperature was measured every 1000 m of sliding distance via three-point infrared thermometer, to examine the effect of temperature variations. The sample surfaces were also examined in optic microscope after the experiments. Higher friction coefficient values were obtained in the normal direction-oriented carbon fiber specimen. Findings: Comparing the friction coefficient values, antiparallel and parallel direction-oriented carbon fiber specimens gave lower friction coefficient values. The increase of sliding velocity and normal load resulted in the increase of surface temperature and this lead to the increase of friction coefficient. Originality/value: This study shows the effects of fiber orientation on the tribological behavior of carbon fiber–reinforced epoxy composite. According to fiber orientations, relatively moving counter surfaces of this material shows different tribological behaviors.